Scaling Climate-Smart Agriculture Through Interdisciplinary Research-for Development: Learning from South and Southeast Asia’s Rice-Based Systems In book - Hellin, Jonathan; Fisher, Eleanor; Balie, Jean; Sander, Björn Ole; Kohli, Ajay (Springer, 2021)
"Climate change will have a largely detrimental impact on the agricultural sector. Reduced yields will lead to greater food insecurity and a rise in food prices. In response, researchers have developed agricultural technologies and practices, commonly known as climate-smart agriculture (CSA). Scaling or large-scale farmer uptake of CSA is often seen as the responsibility of development practitioners. This, however, encourages a false dichotomy between knowledge generation through “research” and practice-based “scaling.” Such binary thinking poses two dangers. Firstly, when faced with donors’ understandable wish to see impact on the ground, agricultural research organizations succumb to “mission drift” and engage in “development work,” for which they have little comparative advantage. Secondly, because scaling is seen as a “development” as opposed to “research” issue, the contribution that research can make to understanding effective scaling is overlooked. We propose that agricultural research-for-development (AR4D) can contribute more to scaling by conceptualizing the process as a multifaceted one that catalyzes three interconnected and complimentary pathways: technology development, capacity development, and policy influence, each overseen by interdisciplinary research teams. We use our experience from rice based systems in South and Southeast Asia to illustrate how a combination of all three pathways is required to enhance scaling of CSA."